Impact of an industry dominated Shivalik watershed on farm economy, livelihoods, groundwater depletion and possible remediation measures - GREWAL, S.S. (Journal of Soil and Water Conservation, 2026)
The industrial pollution has become a major environmental problem defying solution. A 3256 ha watershed located in the Shivalik foot hills of Solan district of Himachal Pradesh gradually came under state promoted industrial development with a provision of incentives and subsidies. As the industry expanded, it created the serious problem of groundwater depletion, pollution by untreated sewage water as pollution control norms were not strictly followed. The agriculture and livelihoods of the watershed communities were largely affected. A corporate supported study was conducted during 2022-23 to analyze the cause and effects of these problems and scope of sustainable and environment friendly development. The study indicated that the untreated polluted water was discharged into the Sirsa rivulet which carried it to Satluj river and ended up polluting waters of Ramsar Wetland at Ropar head works and resulting in death of fish and migratory birds. As the big pharmaceutical industries installed large size deep bore well to extract groundwater, the water level of relatively shallow agricultural bore-well (55 Nos) in adjoining 21 villages started drying up. The water level drop varied from 8 to 25 m in last 15 years and farmers were compelled to add more pipes, opted for submersible motors and increase their horse power at a huge cost. The bore wells for drinking water managed by Public Health wing and those of Industrial Development Corporation for industrial water supply were installed in perennial drainage lines of the watershed which extracted all run-off water before recharging the groundwater leading to groundwater depletion. Paradoxically, the major part of the extracted ground water by industry was again discharged as polluted water in the drainage lines and lost as runoff from the watershed to Sirsa rivulet creating another problem. The survey revealed that 21 villages (2246 ha) adjoining the industrial estate and 11678 people came under strong influence of industry where farmer’s interest in agriculture and animal husbandry decreased. Industry did not employ more locals because of the fear of forming trade unions and thus employed outsiders. As part of private lands was purchased by the industry, people spent the money to add additional rooms in houses to give on rent. Many landless have opened small shops; some farmers purchased trucks and tempos for transport of industrial goods and tankers for supply of drinking water. The livelihood base shifted from agriculture to other jobs. The water balance study indicated that the average annual recharge was 1014 ham, the extraction of groundwater by 55 agricultural bore wells, tube well installed for drinking water supply and tube wells installed for water supply to industries was 779.17, 480.92 and17.42ham respectively making a total of 1277.51 ham leaving annual deficit of 263.51 ham leading to lowering of water table. As possible phyto-remediation remedial measures, the polluted water of Kotla choe is proposed for treatment through locally available Vetiver grass (Vetiver zizanioides). The tertiary treated water could be used for irrigation for a proposed plantation block and a park situated nearby. The problems due to disposal of toxic water in Ramsar Wetland were highlighted and need based and demand driven soil and water conservation measures including rainwater harvesting for groundwater recharge has been suggested with proper sites and design norms. It is proposed to develop Baddi as a model for industry dominated watersheds for sustainable livelihoods of local communities.